Ecopolitics Podcast, Episode 4: Environmental Racism and Justice in Canada - Katz-Rosene, Ryan; Andrée, Peter (Université d'Ottawa | University of Ottawa, 2020)
Racism and colonialism are deeply entrenched in the field of ecopolitics. In this episode, we talk with Dr. Andil Gosine, professor in the Faculty of Environmental and Urban Change at York University, and Tzazná Miranda Leal, Workers Rights Organizer and Community Artist with Justice For Migrant Workers about the ways in which racism is woven throughout Canadian environmental history and its impacts on Canadian environmental policy and research. [Produced by Nicole Bedford; Artwork by Adam Gibbard; Transcription by Kika Mueller].